2016
DOI: 10.3892/ijo.2016.3589
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA HOTAIR modulates HLA-G expression by absorbing miR-148a in human cervical cancer

Abstract: Abstract. The long non-coding RNA HOX transcript antisense RNA (HOTAIR) has been found overexpressed in many human malignancies and involved in tumor progression and metastasis. However, little is known about the potential biological roles of HOTAIR in tumor escape. In the present study, the expression of HOTAIR was detected in 59 paired cervical cancer tissue samples by real-time PCR and then subjected to correlation analysis with clinical features. The effects of HOTAIR on cervical cancer cells as well as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 41 publications
(40 reference statements)
2
38
0
Order By: Relevance
“…This study investigated the ability of HOTAIR in differentiating benign thyroid nodules from malignant nodules (NCT03469544). As reviewed above, HOTAIR upregulates the expression of HLA-G in tumor tissues (47,57), which indicated the potential role of HOTAIR as a biomarker of tumor immune escape. Other lncRNAs that regulate the pivotal molecules and pathways that are targeted in clinical therapies, such as tumor vaccine, T cellbased therapy, and ICB, can also potentially predict response to tumor immunotherapy.…”
Section: The Preclinical and Clinical Applications Of Lncrnas In Cancmentioning
confidence: 87%
“…This study investigated the ability of HOTAIR in differentiating benign thyroid nodules from malignant nodules (NCT03469544). As reviewed above, HOTAIR upregulates the expression of HLA-G in tumor tissues (47,57), which indicated the potential role of HOTAIR as a biomarker of tumor immune escape. Other lncRNAs that regulate the pivotal molecules and pathways that are targeted in clinical therapies, such as tumor vaccine, T cellbased therapy, and ICB, can also potentially predict response to tumor immunotherapy.…”
Section: The Preclinical and Clinical Applications Of Lncrnas In Cancmentioning
confidence: 87%
“…Loss-of-function experiments indicated that overexpression of HOTAIR promoted, whereas silencing of HOTAIR inhibited growth, invasion, and cell viability of CaCx cells in vitro and in vivo. Moreover, HOTAIR modulated the expression of human leucocyte antigen-G by competitively binding to miR-148a; this effect suggests that HOTAIR played an important oncogenic role in CaCx and might serve as a biomarker and a potential target to determine prognosis, as well as a therapeutic intervention for CaCx [96]. Pearson's correlation analysis indicated the negative correlation between the expression levels of miR-17-5p and HOTAIR.…”
Section: Hotair In Cervical Cancermentioning
confidence: 91%
“…Elevated HOTAIR was associated with advanced tumor stage, lymphatic node metastasis, recurrence, and short OS. Thus, circulating HOTAIR may be used as a potent prognostic marker in patients with CaCx [94][95][96]. Loss-of-function experiments indicated that overexpression of HOTAIR promoted, whereas silencing of HOTAIR inhibited growth, invasion, and cell viability of CaCx cells in vitro and in vivo.…”
Section: Hotair In Cervical Cancermentioning
confidence: 99%
“…As is known, lncRNAs can also function as miRNA sponge in thyroid cancer [27], cervical cancer [28] and gastric cancer [29]. We speculated that LOC100507600 might competitive bind to the miR128-1-3p, thereby stopping its target RNA from suppression.…”
Section: Loc100507600 Influences Cell Migration and Cell Proliferatiomentioning
confidence: 99%